Improving MSMEs with digital business-based community empowerment model in Pangandaran region, Indonesia: A system dynamics perspective - Novita, Asti Amelia; Wismanu, Rendra Eko; Wahyudi, Lestari Eko (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
The creative economy has become Indonesia's new potential after being included in the national development strategic plan. In 2007, creative economy program was started by the Indonesian Agency for Creative Economy and has now merged into the program of Ministry of Tourism and Creative Economy (Kemenparekraf). This study aims to build a digital business-based community empowerment model to improve MSMEsâ€™ resilience in the midst of pandemic. A qualitative approach and system dynamics model were used to investigate the handicraft sector in Pangandaran Regency. This study found that MSMEs in Pangandaran Regency still relied on government support. Also, the handicrafts creation was still below the standard and the quantity was not sufficient. Moreover, the business actors still lacked the capital. This condition was exacerbated by the lack of use of digital marketing by craftsmen. Efforts made by the government were intensive assistance. Although it was still quite far from what was expected, the programs implemented by the relevant agencies were quite significant. Even though the penta-helix synergy has been performed to develop MSMEs in Pangandaran Regency, there were some stakeholders that had not optimally implemented their functions.JEL ClassificationÂ C26; I26; J15